2018
DOI: 10.1111/nph.15484
|View full text |Cite
|
Sign up to set email alerts
|

Parental transposable element loads influence their dynamics in young Nicotiana hybrids and allotetraploids

Abstract: The genomic shock hypothesis suggests that allopolyploidy is associated with genome changes driven by transposable elements, as a response to imbalances between parental insertion loads. To explore this hypothesis, we compared three allotetraploids, Nicotiana arentsii, N. rustica and N. tabacum, which arose over comparable time frames from hybridisation between increasingly divergent diploid species. We used sequence-specific amplification polymorphism (SSAP) to compare the dynamics of six transposable element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 65 publications
5
29
0
Order By: Relevance
“…When hybridization and polyploidy are combined, this can lead to TE bursts in the genome. As originally proposed by Barbara McClintock, allopolyploidization produces a "genomic shock", a genome instability associated with the relaxation of the TE silencing mechanisms and the reactivation of ancient TEs (McClintock 1984;Mhiri et al 2019). Hybridization, polyploidy and asexual reproduction are combined in M. incognita with relative effects on the TE load extremely challenging, if not impossible, to disentangle.…”
Section: Fig 5: Categories Of Polymorphic Te Locimentioning
confidence: 99%
“…When hybridization and polyploidy are combined, this can lead to TE bursts in the genome. As originally proposed by Barbara McClintock, allopolyploidization produces a "genomic shock", a genome instability associated with the relaxation of the TE silencing mechanisms and the reactivation of ancient TEs (McClintock 1984;Mhiri et al 2019). Hybridization, polyploidy and asexual reproduction are combined in M. incognita with relative effects on the TE load extremely challenging, if not impossible, to disentangle.…”
Section: Fig 5: Categories Of Polymorphic Te Locimentioning
confidence: 99%
“…The merger of two distinct genomes in one allopolyploid nucleus may result in ‘genomic shock’ [7], which yields changes in gene expression [8–12], chromosomal rearrangements [13, 14], increase of transposable element activity [15, 16], alterations of physiological processes [17, 18], changes in morphology [19, 20], and niche shifts [21]. These processes and their results can isolate newly formed allopolyploids from their diploid progenitors and may facilitate their establishment as a new species.…”
Section: Introductionmentioning
confidence: 99%
“…Lim et al (2004) suggested that greater imbalance is leading to stronger genome shock intensity. Recently, Mhiri et al (2019) found that the proportion of new loci correlates with the extent of each TE load imbalance in different Nicotiana accessions and thus supported the influence of the genome shock intensity on TE activation. Genome dominance at the genomic level may be achieved by different regulation and composition of dominant TEs in the parental lineages (Freeling et al, 2012).…”
Section: Genomic Changes and Te Dynamics In Allopolyploidsmentioning
confidence: 77%